ILMU BERMANFAAT: DALAM PERSPEKTIF IMAM BURHANUL ISLAM AZ-ZARNUJI - Abdul Manan; Oyoh Baria; Khalid Ramadhan (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
The role of Islamic boarding schools is very good in creating the next generation of a superior nation, judging by the history of the independence of the Republic of Indonesia, all Islamic boarding schools, both clerics and students, all participated in liberating the Indonesian nation. Therefore, in the Islamic boarding school environment there are many positive things so that until now scholars and students still exist and are ready to defend independence. Defending independence is not only by fighting against the invaders, but also fighting to eliminate the ignorance of oneself and others, including defending the independence of the nation. Almost in Islamic boarding schools throughout Indonesia, especially Java, the scholars teach their students so that later their knowledge can be useful for others. This research is a qualitative research by analyzing the main source, namely the Ta'limu Ta'allim book which contains how a student can get the benefits and blessings of knowledge. According to Imam Burhanul Islam Az-Zarnuji to obtain useful knowledge, namely with 6 conditions, namely intelligence, enthusiasm, patience, provision, instructions from the teacher and must be with a long time.